An Ancient Pact: A Psychoanalytic Study on The Image of The Devil in The Novel Belleǧin Kış Uykusu - Seda Çetin (İstanbul Üniversitesi Edebiyat Fakültesi Türk Dili ve Edebiyatı Dergisi)
In all cultures and religions, the concept of the Devil has some features in common with all humanity. In the scriptures, the Devil’s pacts made with God and ordinary mortals are notable. In fiction, the Devil became a new person in Mehmet Eroğlu’s Belleğin Kış Uykusu, as a character in the movie The Student of Prague, and thus they are examples of the “pact with the Devil” motif. It is important to focus on why the Devil image appeared in these fictional works to receive the messages these works want to convey. The analysis of this image is made possible by considering important concepts of psychoanalysis, such as collective unconscious, archetype, alienation, other, symbolic, “mirror phase” id–ego–superego, and self. Baudrillard’s comment on The Student of Prague in The Consumer Society supports this work which focuses on the novel, to understand the Devil image better. The most important reason for referring to the movie in interpreting the novel is that the two fictional works deal with the “pact with the Devil” motif and the said pact had similar effects on the personalities of the human characters portrayed. When these results, which are expressed in one case metaphorically and the other literally, are comparatively considered, they also undertake the task of explaining each other. Because of comparative psychoanalytic readings, it has been observed that the “pact with the Devil” theme in Belleğin Kış Uykusu indicates a serious self problem through the implicit and explicit “mirror image” references in both works.